2003
DOI: 10.1196/annals.1299.052
|View full text |Cite
|
Sign up to set email alerts
|

ICBP90 Expression Is Downregulated in Apoptosis‐Induced Jurkat Cells

Abstract: Inhibition of apoptosis, resulting from an increase in anti-apoptotic protein, plays a fundamental role in carcinogenesis. Because ICBP90 gene expression is deregulated in cancer cells, we studied its expression in Jurkat cells under apoptotic conditions to see whether ICBP90 is involved in the regulation of apoptosis. We found that ICBP90 expression and the percentage of living cells were dose-dependently decreased in PHA and ionophore A23187-stimulated Jurkat cells, but not in THP-1 cells. These results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
4
10
0
Order By: Relevance
“…UHRF1 appears therefore to have in our experimental settings antiapoptotic properties, in agreement with previous observations [10,15,21]. One interesting idea therefore is that preventing the epigenetic code to be replicated after UHRF1 deregulation leads to the activation of an apoptotic pathway.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…UHRF1 appears therefore to have in our experimental settings antiapoptotic properties, in agreement with previous observations [10,15,21]. One interesting idea therefore is that preventing the epigenetic code to be replicated after UHRF1 deregulation leads to the activation of an apoptotic pathway.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our hypothesis, it has been shown that the activation of different cell cycle checkpoints during DNA damage-induced apoptosis leads to a down-regulation of UHRF1 [9]; such deregulation has been described to be dependent on the p53/p21 WAF1/CIP1 pathway [14]. It should be noted that reduction of UHRF1 expression solely can suppress proliferation and induce apoptosis of cancer cells whose p53 is inactivated [15]. This suggests that UHRF1 functions as a component in the DNA damage response pathways and that it plays a role in the maintenance of genomic stability.…”
Section: Introductionsupporting
confidence: 89%
“…Ubiquitin-like with plant homeodomain and ring finger domains, 1 (UHRF1), also known as Np95 or ICBP90 [14, 15], is a nucleoprotein associated with tumorigenesis [16, 17]. Researchers found that UHRF1 regulates gene expression and chromatin modification by interacting with DNA methyltransferase 1 and histone deacetylase 1 [1820], and UHRF1 overexpression drives DNA hypomethylation and oncogenesis [21].…”
Section: Introductionmentioning
confidence: 99%
“…These defects suggest that uhrf1 is required for hepatocyte proliferation. Additional studies in tissue culture cells demonstrate that UHRF1 depletion causes cell cycle arrest (Bonapace et al , 2002; Jenkins et al , 2005; Tien et al , 2011), hypersensitivity to DNA damage and chemotherapeutic agents (Muto et al , 2002; Arima et al , 2004), or apoptosis (Abbady et al , 2003; Tien et al , 2011). Conversely, high levels of UHRF1 are found in a number of human cancer cell lines (Mousli et al , 2003; Jenkins et al , 2005) and primary tumors (Hopfner et al , 2000; Crnogorac-Jurcevic et al , 2005) and, in some cell types, overexpression of UHRF1 increases cell proliferation (Hopfner et al , 2002; Jenkins et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in uhrf1 mRNA (Sadler et al , 2007), protein (Bonapace et al , 2002; Arima et al , 2004; Brunet et al , 2008; Kim et al , 2009), and localization (Uemura et al , 2000; Miura et al , 2001; Kim et al , 2009) accompany different cell cycle stages in some cells, but in others, most notably in cancer cells, UHRF1 levels do not change dramatically during the cell cycle (Mousli et al , 2003; Arima et al , 2004; Bronner et al , 2007). UHRF1 expression is controlled by key cell cycle regulators, including the Rb/E2F complex (Abbady et al , 2003), p53/p21 Cip1 (Arima et al , 2004), and the E1A transcription factor (Bonapace et al , 2002). We hypothesize that other factors that act during the cell cycle may provide an additional level of regulation of UHRF1.…”
Section: Introductionmentioning
confidence: 99%